A Nonaqueous Approach to the Preparation of Iron Phosphide Nanowires - She Houde; Chen Yuanzhi; Wen Ruitao; Zhang Kui; Yue Guang-Hui; Peng Dong-Liang (Nanoscale Research Letters, 2010)
Abstract Previous preparation of iron phosphide nanowires usually employed toxic and unstable iron carbonyl compounds as precursor. In this study, we demonstrate that iron phosphide nanowires can be synthesized via a facile nonaqueous chemical route that utilizes a commonly available iron precursor, iron (III) acetylacetonate. In the synthesis, trioctylphosphine (TOP) and trioctylphosphine oxide (TOPO) have been used as surfactants, and oleylamine has been used as solvent. The crystalline structure and morphology of the as-synthesized products were characterized by powder X-ray diffraction (XRD) and transmission electron microscopy (TEM). The obtained iron phosphide nanowires have a typical width of ~16 nm and a length of several hundred nanometers. Structural and compositional characterization reveals a hexagonal Fe2P crystalline phase. The morphology of as-synthesized products is greatly influenced by the ratio of TOP/TOPO. The presence of TOPO has been found to be essential for the growth of high-quality iron phosphide nanowires. Magnetic measurements reveal ferromagnetic characteristics, and hysteresis behaviors below the blocking temperature have been observed.